Abstract The effect of media and social media on security and reducing crime from the perspective of some high school students in Riyadh - al-Hariri, Ahmed Said (Journal of Educational and Psychological Sciences, 2019)
The current study aimed to investigate the role of media and social media on security and reducing crime. This research used a descriptive mixed-methods approach, by using two instruments: a questionnaire and an interview. The questionnaire was administrated on a survey sample of students (n = 390) and 12 students were interviewed qualitatively, which all are in high school in Riyadh. Results showed that the effect of media and social media on security and crime reduction was (M = 2.41 out of 3) in general and this is a large effect. The influence of media role in implementing security in its comprehensive concept was (M = 2.24 out of 3), which is a medium effect. The influence of social media on internal security (M = 2.32 out of 3), which is a medium effect. The influence of distributing security information in different media (M = 2.50 out of 3), which is a large effect. The influence of using social media in security media (M = 2.55 out of 5) which is a large effect. The influence of social media on media and in forming the general opinion (M = 2.37 out of 3) which is a large effect. The mean of the best way to deal with websites and electronic forums was (M = 2.47 out of 3) which is a large effect. The mean of the role of modern technology in security media (M = 2.43 out of 3) which is a large effect. The results of the qualitative interviews matched the findings of the quantitative data. A number of important comments and clarifications were added. The research concluded with a number of recommendations that stress the role of media and social media on the occurrence of crime, as well as their role in reducing crime at the same time. Especially when considering the youth attitudes toward using social media.